2021
DOI: 10.1108/intr-08-2020-0482
|View full text |Cite
|
Sign up to set email alerts
|

The role of flow consciousness in consumer regret

Abstract: PurposeThis research aims to identify whether subsequent consciousness of having been in a flow state – that is, flow consciousness – regarding an earlier impulse purchase affects consumers' post–purchase behaviours, specifically their feelings of consumer regret.Design/methodology/approachThe study applied a mixed methodology. First, the authors conducted two qualitative studies (focus groups) to establish the relationships between flow, flow consciousness and regret. Second, the authors conducted a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 77 publications
0
15
0
1
Order By: Relevance
“…E-commerce has drastically changed the traditional buyer-seller relationship and the shopping process for many consumers (Flavi an-Blanco et al, 2011;Lo et al, 2016;Widyawati and Ariyanti, 2017). Today, in the digital era, consumers can browse and compare endless product catalogs, create wish lists and enjoy powerful features such as search and personalization and social networks (Barta et al, 2021b). In the context of online shopping, the utilitarian motive is related to the purchase of an object for its functional value, whereas the hedonic motive concerns the emotional experiences of the online shopping process itself (Fernandes et al, 2020).…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…E-commerce has drastically changed the traditional buyer-seller relationship and the shopping process for many consumers (Flavi an-Blanco et al, 2011;Lo et al, 2016;Widyawati and Ariyanti, 2017). Today, in the digital era, consumers can browse and compare endless product catalogs, create wish lists and enjoy powerful features such as search and personalization and social networks (Barta et al, 2021b). In the context of online shopping, the utilitarian motive is related to the purchase of an object for its functional value, whereas the hedonic motive concerns the emotional experiences of the online shopping process itself (Fernandes et al, 2020).…”
Section: Literature Review 21 Theoretical Backgroundmentioning
confidence: 99%
“…Further, a study conducted in an online shopping context by Shahpasandi et al (2020) showed that flow experience and hedonic browsing significantly influence customers' impulsive buying. Simultaneously, (Barta et al, 2021b) asserted the significance of hedonic motive in enhancing the impulsive shopping tendency of the online shoppers based on the ease and comfort provided by the digital media channels. Therefore, the following is hypothesized:…”
Section: Sjme 262mentioning
confidence: 99%
“…As such, the free-to-play business model per se is not harmful or conducive to player attrition, but instead ambiguous communication and aggressive monetization seem to be the main sources of negative implications. To ensure meaningful gameplay experiences, managers and game developers alike should gain in-depth understanding on why and for what purposes people play their games (see also Barta et al 2021 ). As one of the practitioner participants put it, mobile games—and digital services more broadly—need to create genuine value for the players to get them committed.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting frequency was compared to the theoretical framework, thereby excluding the words that were not conceptualized. For a clear visualization of the distinctions between the main concepts found in the focus groups and the phrases that represent these concepts, the results are presented in tables, as suggested by Barta et al (2022). In the following section, the analysis reveals that all three focus groups answered similarly.…”
Section: Factors That Make a Destinationmentioning
confidence: 95%